2014
DOI: 10.1016/j.jnci.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Gastric carcinoma at Tanta Cancer Center: A comparative retrospective clinico-pathological study of the elderly versus the non-elderly

Abstract: Compared to the non-elderly, GC in the elderly has similar clinico-pathological characteristics and exhibits comparable outcomes with the same treatment options. Treatments should be tailored to each patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
3
5
1
Order By: Relevance
“…We found that intestinal-type adenocarcinoma accounts 63.5% of our cases, which is consistent with the reported data by Zeeneldin et al [16], was 47.6%. Most of our cases belong to moderately differentiated tumours (58.9%), which is in contrast to the other study, that they reported 58.1% of cases belong to tumours with G-III /IV [16]. …”
Section: Discussionsupporting
confidence: 93%
“…We found that intestinal-type adenocarcinoma accounts 63.5% of our cases, which is consistent with the reported data by Zeeneldin et al [16], was 47.6%. Most of our cases belong to moderately differentiated tumours (58.9%), which is in contrast to the other study, that they reported 58.1% of cases belong to tumours with G-III /IV [16]. …”
Section: Discussionsupporting
confidence: 93%
“…The PYLL and DALY rates for the elderly in the present study were more than two times those of the young, which was probably related with the large number of deaths in the elderly. Other studies have reported similar results, with >80% of cancer deaths occurring in the elderly [ 29 ]. Cancer-related mortality in the elderly in the present study was 13.53 times that of the young.…”
Section: Discussionsupporting
confidence: 73%
“…According to a recent Egyptian study, the median overall survival, disease-free survival and progression-free survival for GC patients are 6, 17 and 3 months, respectively [16].…”
Section: Discussionmentioning
confidence: 99%